A formal theory can explain disjunctive illusory inferences. - López Astorga, Miguel (Círculo de Lingüística Aplicada a la Comunicación, 2014)
There are disjunctive inferences that can be considered to be illusory, since, when faced to them, people tend to draw logically incorrect conclusions. The mental models theory can explain this problem by distinguishing between mental models and fully explicit models. According to it, individuals often derive only conclusions compatible with the mental models, and not with the fully explicit models. However, I try to show in this paper that a syntactic approach can also account for the problem of the mentioned inferences. It is enough to assume that disjunctions are basically inclusive and that exclusive disjunctions require resorting to more complex formulae.